(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Oxidative stress affects all structures of the human eye with its special emphasis on the ocular surface, lens and retina contributing to the onset or progression of eye diseases. Age-related ocular pathologies including are largely mediated by the oxidative stress thus highlighting the need to enlighten a preventive measure that can address oxidative stress and slow the progression of age-related ocular pathologies. Aims and Objective: Saptamrutha Lauha is formulation of seven drugs which could act as Rasayana and Chakshushya so here they are hoped for an antioxidant network activity. Methods: 36 male Wistar albino rats were divided into 6 groups. Single dose of Naphthalene was administered orally for all groups, except the control group on first day. Group I: control, Group II: Silymarin administered orally for 10 days. Group III, IV and V: low, medium, high doses of Saptamrutha Lauha respectively administered orally for 10 days. Group VI: naphthalene group, treated with naphthalene alone. After 10th day rats were sacrificed, antioxidant effect was analyzed from serum biochemical parameters and also from antioxidant assays. Observation and Analysis: Saptamrutha Lauha at all three doses (low dose, intermediate dose, high dose) were found to be effective in antioxidant activity. Discussion and Conclusion: The assays done suggests that Saptamrutha Lauha is capable of scavenging free radicals evolved in the pathogenesis of Naphthalene induced oxidative stress. Thus, this study provides a scientific basis for usage of Saptamrutha Lauha as an antioxidant.